Relationships among precipitation regime, nutrient availability, and carbon turnover in tropical rain forests (2011)
The effect of high precipitation regime in tropical forests is poorly known despite indications of its potentially negative effects on nutrient availability and carbon (C) cycling. Our goal was to determine if there was an effect of high rainfall on nitrogen (N) and phosphorous (P) availability and indexes of C cycling in lowland tropical rain forests exposed to a broad range of mean annual precipitation (MAP). We predicted that C turnover time would increase with MAP while the availability of N and P would decrease. We studied seven Neotropical lowland forests covering a MAP range between 2,700 and 9,500 mm. We used radiocarbon ({increment}14C) from the atmosphere and respired from soil organic matter to estimate residence time of C in plants and soils. We also used C, N, and P concentrations and the stable isotope ratio of N (?15N) in live and dead plant tissues and in soils as proxies for nutrient availability. Negative ?15N values indicated that the wettest forests had N cycles that did not exhibit isotope-fractionating losses and were potentially N-limited. Element ratios (N:P and C:P) in senescent leaves, litter, and live roots showed that P resorption increased considerably with MAP, which points towards increasing P-limitation under high MAP regimes. Soil C content increased with MAP but C turnover time only showed a weak relationship with MAP, probably due to variations in soil parent material and age along the MAP gradient. In contrast, comparing C turnover directly to nutrient availability showed strong relationships between C turnover time, N availability (?15N), and P availability (N:P) in senescent leaves and litter. Thus, an effect of MAP on carbon cycling appeared to be indirectly mediated by nutrient availability. Our results suggest that soil nutrient availability plays a central role in the dynamic of C cycling in tropical rain forests. © 2011 Springer-Verlag.